KAJIAN OPTIMALISASI POTENSI PRODUK UNGGULAN DAN EKONOMI LOKAL DENGAN PRINSIP EKONOMI HIJAU, EKONOMI BIRU, DAN EKONOMI PARIWISATA KABUPATEN MAJENE PROVINSI SULAWESI BARAT - Misbahuddin Misbahuddin (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2018)
The purpose of this research is to provide superior and competitive product information of each region and sub-district, as well as the community's readiness to take a role in the process of developing the economic potential associated with the Five-Year Development Plan Document (RPJMD), so that there is a sustainable economic development model can be run by Majene Regency government. The result of this research is the optimization of local economic development and regional superior product, the application of green revolution policy in Majene District can be reached by determining the agropolitan area should be placed in Malunda and Ulumanda subdistricts sebegai agropolitan area of ​​commodity of rice and corn. Other agropolitan areas can be placed in Tammerodo Subdistrict for cassava commodities and Determination of minapolitan areas can be set in District Banggae, District Pamboang, District Sendana, and District Tubo Sendana, through the concentration of marine and fisheries development in Lereklerenkan Island, and increase the number of business families sea ​​cultivation in Tubo Sendana sub-district and other sub-districts including minapolitan area